Bibliometric trends of scientific publications on antimicrobial resistance in Escherichia coli in Peru from 2009-2019. - Ruiz , Joaquim (2022)
Antibiotic resistance is a growing problem worldwide. While the most visible aspect is the direct effect of antimicrobial resistance in clinical settings, this problem affects all microorganisms in all environments. Nevertheless, most of the data available on antibiotic resistance outside clinical settings are from high-income countries, with the current situation in most low- and middle-income countries remaining under-reported. Escherichia coli is considered a good marker of “antibiotic pressure” due to its cosmopolitan distribution. In this scenario, we selected E. coli as an appropriate microorganism to perform an initial bibliometric analysis of publications focused on antimicrobial resistance outside disease-causing microorganisms. Thus, the present manuscript performs an analysis of the studies reporting measurable levels of antibiotic resistance of E. coli not causing human disease in Peru published during the period from 2009-2019. Following a search in PubMed and Google, 35 documents were selected as reporting measurable data of antibiotic resistance. Of these, 8 (22.8%) were reported in thesis format. The mean delay between sampling and publishing in article format was 3.7 years, with one study having been published 18 years after sampling. The number of publications developed in Peru describing antimicrobial resistance levels in E. coli out of hospital settings in the period 2009-2019 is scarce. Of these, a relevant number is of unpublished thesis. These findings showing the gap of knowledge and lack of accessible data about antimicrobial resistance out of hospital environments. Efforts and strategies must be developed to fill this knowledge gap.